Factors that Affect the Intention to Use E-learning among University Lecturers - Titiek Murniati, Cecilia; Hartono, Heny; Cahyo Nugroho, Agus (KnE Social Sciences, 2022)
University lecturers are one among many people who have been affected by the pandemic. Lecturers were forced to use a learning management system, grapple with video conferencing software, and cope with various unpredictable technical issues. In short, external forces seem to pressure lecturers to refine their digital skills and use e-learning as the only way to deliver the materials whenever they were unable to meet face-to-face with students. This study investigates what factors determined lecturers’ intention to use e-learning in their classes. The results of this study suggest that technology literacy and attitude have positive correlations with lecturers’ intention to use e-learning. Keywords: intention to use e-learning; attitude; self-efficacy; technology; literacy; technology comfort level